Investing for Change : Profit from Responsible Investment. - Landier, Augustin (Oxford University Press, 2008)
The socially conscious citizen worries that globalization seems to grind social standards ever lower. Workers earn less, the environment suffers, health care declines. Investing for Change shows that socially conscious citizens can change the globalized world in the direction of many common values by being a socially conscious investor. Categorizing investors in illuminating groups of Yellow, Blue, and Red, and drawing on the latest research and deep experience in asset management, Landier and Nair show how responsible investing can truly come into its own.